Land Development Process in Urban River Areas: A Case in Palangka Raya City, Indonesia - Guntur, Mandarin; Wijaya, Nurrohman; Yunitha, Yunitha (Journal of Regional and City Planning, 2024)
Land development in Indonesia has undergone significant formal and informal changes that affect urban planning and development. Most studies discuss the issue of land development in urban mainland and coastal areas, while fewer studies explain this process in the context of river-based urban regions. This paper describes physical and non-physical factors that drive land development processes, both formally and informally, in urban river areas, including built-up area conditions, land status, involved agents, institutions, and market mechanisms. Researchers selected the Old Town area along the Kahayan River in Palangka Raya City as the study area. This study collected spatial data and reports, conducted field observations, and conducted interviews. Researchers used spatial, descriptive, and content analyses to analyze the data. Aspects of the land market, namely land transactions, land prices, values, and supply-demand issues, were obtained based on secondary data. Physical and non-physical factors of land development were analyzed based on the review of transcripts from in-depth interviews, especially those related to the built-up area conditions, land status, land-use pattern, and infrastructure needs. This study revealed that the government concentrates on formally developing land within the primary infrastructure system through intervention and support from the private sector, which leads to influence of market mechanisms. In contrast, informal land development occurs without the private sector’s intervention or government policies. This study recommends increasing local community capacity to understand formal and informal land development processes by supporting infrastructure development, improving institutional capacity, allocating land development zones, and strengthening urban policies and regulations.